2022
DOI: 10.3390/joitmc8040209
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Community Participation in Environmental Corporate Social Responsibility Projects: Evidence from Mangrove Forest Management Project

Abstract: Community participation in an environmental corporate social responsibility (CSR) project can help business enterprises effectively develop projects that respond to the actual demands of the community and effectively utilize a firm’s resources. This study aims to investigate factors that affect community participation in each stage of environmental corporate social responsibility project development. The environmental corporate social responsibility project explored in this study is a sustainable mangrove fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 97 publications
1
6
0
2
Order By: Relevance
“…Both excellent and effective institutions will ensure sustainable use and management. Local institutions have shown that the success of community forest management cannot be based on the strength of values and norms profoundly rooted and widely accepted by the community (Ostrom 1998;Sattayapanich and Janmaimool 2022). Steenblik (1998) stated that local communities possess the authority to establish regulations, execute judgments, and ensure adherence to rules in various domains of natural resource management.…”
Section: Performancementioning
confidence: 99%
“…Both excellent and effective institutions will ensure sustainable use and management. Local institutions have shown that the success of community forest management cannot be based on the strength of values and norms profoundly rooted and widely accepted by the community (Ostrom 1998;Sattayapanich and Janmaimool 2022). Steenblik (1998) stated that local communities possess the authority to establish regulations, execute judgments, and ensure adherence to rules in various domains of natural resource management.…”
Section: Performancementioning
confidence: 99%
“…Chontanawat y colaboradores (2022) realizan una investigación en la que tratan de averiguar los componentes que pueden influir en la participación de la comunidad en las fases de los proyectos medioambientales de las empresas. La investigación afirma que debido a que muchas empresas tienen un impacto negativo sobre el medioambiente en sus procesos de producción, se creó la responsabilidad social corporativa, que busca contribuir no solo al desarrollo económico, sino también a la calidad de vida de las personas, la comunidad y la sociedad (Chontanawat et al, 2022). Para que las empresas contribuyan a la compensación medioambiental, es necesaria la participación de la comunidad, ya que es a través de ella como se pueden alcanzar los objetivos del proyecto.…”
Section: Participación Comunitariaunclassified
“…With CSR defined as "the continuing commitment by business to behave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as of the local community and society at large" according to the World Business Council for Sustainable Development [8], CSR-projects and initiatives are common practice within business operations of companies in order to assume their responsibility towards society and the stakeholders of their activities. In addition, CSR-programs help companies to gain reputation, customer loyalty, and customer satisfaction [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Different examples of participatory approaches in CSR strategies exist. For example, Appe and Barragán [36] describe how Participatory Action Committees (including community stakeholders and representatives) can be formed to co-design and co-implement CSR practices; Puranik [40] delineates methodological solutions to integrating the participation approach in a CSR plan; Anser et al [39] review how the participatory approach with hotel and tourism managers enhances CSR-practices in terms of their social and environmental impact; and Sattayapanich et al [9] discuss the factors that affect community participation in environmental CSRprojects.…”
Section: Introductionmentioning
confidence: 99%